2018
DOI: 10.3390/toxins10050181
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Cyclophilin Inhibitors Prevent Intoxication of Mammalian Cells with Bordetella pertussis Toxin

Abstract: The Bordetella pertussis toxin (PT) is one important virulence factor causing the severe childhood disease whooping cough which still accounted for approximately 63,000 deaths worldwide in children in 2013. PT consists of PTS1, the enzymatically active (A) subunit and a non-covalently linked pentameric binding/transport (B) subunit. After endocytosis, PT takes a retrograde route to the endoplasmic reticulum (ER), where PTS1 is released into the cytosol. In the cytosol, PTS1 ADP-ribosylates inhibitory alpha sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(70 citation statements)
references
References 59 publications
2
67
0
Order By: Relevance
“…Another example of this difference is the influence of peptidyl prolyl cis ‐ trans isomerases on the intoxication process: These enzymes are required for the activity of endosome‐translocating ADPRTs (Barth, ; Ernst et al, ) but are dispensable for the cellular activity of Ctx (Burress et al, ). Interestingly, peptidyl prolyl cis ‐ trans isomerases do appear to be involved with Ptx intoxication (Ernst et al, ). These collective observations support a general role, with toxin‐to‐toxin differences, for Hsp90, Hsc70, and peptidyl prolyl cis ‐ trans isomerases in A chain translocation for the family of ADPRTs.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of this difference is the influence of peptidyl prolyl cis ‐ trans isomerases on the intoxication process: These enzymes are required for the activity of endosome‐translocating ADPRTs (Barth, ; Ernst et al, ) but are dispensable for the cellular activity of Ctx (Burress et al, ). Interestingly, peptidyl prolyl cis ‐ trans isomerases do appear to be involved with Ptx intoxication (Ernst et al, ). These collective observations support a general role, with toxin‐to‐toxin differences, for Hsp90, Hsc70, and peptidyl prolyl cis ‐ trans isomerases in A chain translocation for the family of ADPRTs.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatically active (A) subunit of PTX, PTS1, detaches from the rest of the toxin in the ER and unfolds due to its thermal instability. It is then transported into the cytosol with the help of cyclophilin (Cyps), an important protein folding helper enzyme that also is required to facilitate membrane translocation from early endosomes into the cytosol of various ADP-ribosylating toxins (311)(312)(313). Inhibiting Cyps activity has been shown to in turn inhibit membrane translocation and protect cells from intoxication with PTX and others (311).…”
Section: Cyclophilin Inhibitorsmentioning
confidence: 99%
“…It has been used as the primary agent in immunosuppressive regimens such as grafts and transplants since the 1980s. It is now suggested that CsA might interfere with the translocation of PTS1 from the ER into the cytosol; it may also play a role in reassembling the unfolded PTS1 subunit (311).…”
Section: Cyclophilin Inhibitorsmentioning
confidence: 99%
“…Both CypA and Cyp40 directly bound to PTS1 in vitro and application of pharmacological Cyp inhibitors such as cyclosporine A (CsA) protected CHO-K1 cells from intoxication with PT. In the presence of Cyp inhibitor, less PTS1 reached the cytosol and there was less ADP-ribosylated Giα, implicating that Cyps are required for uptake of PTS1 into the cytosol 29,33 .…”
Section: Introductionmentioning
confidence: 98%
“…We recently demonstrated that specific members of the cyclophilin (Cyp) family, namely CypA and Cyp40 are involved in uptake of PTS1 into the cytosol of target cells 29 . Cyps are members of the peptidyl prolyl cis/trans isomerases (PPIases), which are protein folding helper enzymes that catalyze the rotation of peptide bonds in proteins and assist chaperones such as heat shock protein (Hsp) 90 in protein folding/refolding [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%